EVALUATION OF DIFFERENT PEST MANAGEMENT MODULES FOR THE INSECT PEST COMPLEX OF BRINJAL DURING RABI SEASON IN ZONE - III OF BIHAR - S. TAMOGHNA,; C. NITHYA,; K. RANDHIR, (The Bioscan, 2014)
Field experiment was conducted from 2011 to 2013 to evaluate the effectiveness of different pest management modules against major pest viz. shoot and fruit borer (Leucinodes orbonalis), leaf hopper (Amrasca biguttula biguttula), white fly (Bemisia tabaci) and aphid (Aphis gossypii) of brinjal during rabi season in Zone-III of Bihar. The modules consisted of organic module (M1): soil application of FYM+weekly clipping of infested shoot+ pheromone traps+ Trichogramma chilonis+NSKE+ Bt, IPM module (M2): seedling root dip in imidacloprid +maize border crop+ clipping of infested shoots+ pheromone traps+ cypermethrin, bio-rational module(M3): imidacloprid+thiomethoxam+spinosad+ indoxacarb + emamectin benzoate and untreated check (M4). The impacts of treatments on natural enemies as well as pollinators were also assessed. The results revealed that minimum shoot and fruit (5.10 and 15.18 per cent, respectively) infestation was found in bio-rational module which was followed by IPM module (7.28 and 18.94 cent, respectively). Effectiveness of this module was also reflected on reduction in sucking pest viz white fly (5.68 per 3 leaves), hopper (6.28 per 3 leaves) and aphid (4.34 per 3 leaves) infestation and fruit yield (327.68 q/ha) which was significantly higher in comparison to other modules. However, IPM module (coccinellids: 5.20-7.80 /plant, spiders: 4.80-5.80 /plant and syrphids: 2.70- 4.20 /plant) and organic module (coccinellids: 4.20-6.60 /plant, spiders: 2.80-4.00 /plant and syrphids: 2.00- 2.60 /plant) were safer to natural enemies as well as pollinators. As per as cost benefit ratio is concerned, highest cost benefit ratio was obtained in IPM module (1: 31) followed by bio-rational module (1: 22).